Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1967
DOI: 10.1111/j.1432-1033.1967.tb19520.x
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized Yeast Cells

Abstract: Homogenates and extracts of yeast cells (Saccharomyces cerevisiae) exhibit DNA polymeras activity as revealed by incorporation of labeled dATP into DNAase‐sensitive, RNAase‐resistent acid‐insoluble material, the incorporation being dependent on the presence of all four deoxynucleotide triphosphates and primer DNA. Extracts from synchronized yeast cells exhibit DNA polymerase activity in an oscillating manner during the cell cycle, maximum activity being found just before the onset of DNA replication. Degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1967
1967
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…A similar fluctuation of DNA polymerase activity in cell homogenates has also been observed in synchronized yeast cells in which DNA polymerase activity increases about 2-fold during initiation of DNA synthesis [34,22]. A difference in the specific polymerase activity is also apparent in extracts prepared from growing or resting cells; in a growing cell population in which approximately 30% of the cells are in S-phase, DNA polymerase activity is about 1.4 times higher than in resting cells.…”
Section: Dna-polymerase a C Tivity In Growing And Resting Yeast Cellssupporting
confidence: 60%
“…A similar fluctuation of DNA polymerase activity in cell homogenates has also been observed in synchronized yeast cells in which DNA polymerase activity increases about 2-fold during initiation of DNA synthesis [34,22]. A difference in the specific polymerase activity is also apparent in extracts prepared from growing or resting cells; in a growing cell population in which approximately 30% of the cells are in S-phase, DNA polymerase activity is about 1.4 times higher than in resting cells.…”
Section: Dna-polymerase a C Tivity In Growing And Resting Yeast Cellssupporting
confidence: 60%
“…Unless otherwise indicated, the standard reaction mixture contained, in a final volume of 0.125 ml: 0.05 M Tris-C1, pH 7.5, I0 mM MgCl,, 1 mM EDTA, 2 mM B-mercaptoethanol, 50p.M each of dGTP, dATP, dCTP, and dTTP, 0.25 p.C [3H]dTTP, 13 pg of "activated" salmon sperm DNA and enzyme. 125 pg of phosphoenol pyruvate (trisodium salt) and 10 pg of pyruvate b a s e were added to each assay for the activity determinations of enzyme preparations prior to the DEAE-cellulose chromatography step. After 15 min incubation a t 35", the reaction was stopped by chilling and loo$ of the mixture were applied to discs For crude enzyme solutions this assay is linear up to an amount of about 100 pg of input protein; for more purified preparations, after the DEAEcellulose chromatography step, linearity is observed only up to 20 pg of input protein.…”
Section: Determination Of D N a Polymerase Activitymentioning
confidence: 99%
“…Previously, Eckstein et al (12) had reported that intracellular activity of DNA polymerase in the synchronously cultured cells of S. cerevisiae alters in an oscillating manner with the maximal activity at just before initiation of DNA replication in the cell division cycle. In this report, we found that the intranuclear specific-activity of the polymerase characteristically increases in dependent fashion on prograssion of the cell division cycle, from middle to late Gl phase, with little alteration in cellular activity of the enzyme (specific activity) by using cdc-mutants, cdc 25, cdc 28 cdc 4 and cdc 7.…”
Section: Discussionmentioning
confidence: 99%